2014
DOI: 10.1039/c3mb70440h
|View full text |Cite
|
Sign up to set email alerts
|

Essential gene identification and drug target prioritization in Leishmania species

Abstract: Leishmaniasis is one of the neglected tropical diseases (NTDs), mainly affecting impoverished communities and having varied ranges of pathogenicity according to the diverse spectrum of clinical manifestations. It is endemic in many countries and poses major challenges to healthcare systems in developing countries. Despite the fact that most of the current mono and combination therapies are found to be failures, clear perception of gene essentiality for parasite survival are now desideratum to identify potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Essential genes are those genes of an organism that are critical for its survival; essential genes are of particular importance because of their theoretical and practical applications such as studying the robustness of a biological system (1), defining a minimal genome/organism (2,3) and identifying effective therapeutic targets in pathogens (46) and human cancers (711). In recent years, the technologies used for gene essentiality studies have been evolving rapidly, ranging from low-throughput single gene knockout experiment (12,13) to high-throughput mutagenesis (3), RNAi (7,8) and more recently CRISPR-based genome editing methods (1418); recent studies showed that CRISPR technology outperformed other methods (14,19), featuring low noise and minimal off-target effects (19).…”
Section: Introductionmentioning
confidence: 99%
“…Essential genes are those genes of an organism that are critical for its survival; essential genes are of particular importance because of their theoretical and practical applications such as studying the robustness of a biological system (1), defining a minimal genome/organism (2,3) and identifying effective therapeutic targets in pathogens (46) and human cancers (711). In recent years, the technologies used for gene essentiality studies have been evolving rapidly, ranging from low-throughput single gene knockout experiment (12,13) to high-throughput mutagenesis (3), RNAi (7,8) and more recently CRISPR-based genome editing methods (1418); recent studies showed that CRISPR technology outperformed other methods (14,19), featuring low noise and minimal off-target effects (19).…”
Section: Introductionmentioning
confidence: 99%
“…major strain Friedlin was retrieved from TriTrypDB ( http://tritrypdb.org ) [ 24 ]. InterProScan 4 ( http://www.ebi.ac.uk/Tools/pfa/iprscan/ ) [ 25 ], an online protein functional analysis tool, and PANTHER (Protein ANalysis THrough Evolutionary Relationships; http://www.pantherdb.org/ ) were used to search for a protein signature motif using the respective plugins within Geneious software (Biomatters Ltd, New Zealand) [ 26 , 27 ]. Alignment of the derived amino acid sequences from the different parasites was performed using the ClustalW program in the BioEdit software package (Version 7.0.4.1) and Geneious software [ 28 ].…”
Section: Methodsmentioning
confidence: 99%
“…Given their fundamental roles, it is not surprising that essential genes are the targets of many antimicrobial compounds (Roemer et al 2003;Lu et al 2014;Paul et al 2014). However, the therapeutic implications of essential genes are not fully realized.…”
Section: Potential Applications Of Human Essential Genes In Cancer Rementioning
confidence: 99%